Russia's food security and climate change: looking into the future - Kiselev S; Romashkin R; Nelson, Gerald C.; Mason-D'Croz, Daniel; Palazzo, Amanda (ZBW - German National Library of Economics, 2013)
Global climate change presents long-term risks to agriculture. In general, global climate change is expected to positively affect Russian agriculture. In high and middle latitudes, global warming would expand the growing season. Acreages of agricultural crops may expand toward the north, although yields would likely be lower due to less fertile soil. However, in the south there is a possibility of drier climate, which has a negative impact on crop yields and livestock productivity. In addition, climate change is expected to increase the scarcity of water resources and encourage weed and pest proliferation, and it is expected to increase the short-term risks associated with an increase in extreme weather events and natural disasters. This paper uses data on current conditions to simulate future scenarios and examine possible impacts on crop production in the Russian Federation. It also considers adaptive measures for agriculture in response to climate change.